Total Panax notoginseng saponin inhibits balloon injury-induced neointimal hyperplasia in rat carotid artery models by suppressing pERK/p38 MAPK pathways - Yang,Zheng (2020)
Total Panax notoginseng saponin (TPNS) is the main bioactivity compound derived from the roots and rhizomes of Panax notoginseng (Burk.) F.H. Chen. The aim of this study was to investigate the effectiveness of TPNS in treating vascular neointimal hyperplasia in rats and its mechanisms. Male Sprague-Dawley rats were randomly divided into five groups, sham (control), injury, and low, medium, and high dose TPNS (5, 10, and 20 mg/kg). An in vivo 2F Fogarty balloon-induced carotid artery injury model was established in rats. TPNS significantly and dose-dependently reduced balloon injury-induced neointimal area (NIA) (P<0.001, for all doses) and NIA/media area (MA) (P<0.030, for all doses) in the carotid artery of rats, and PCNA expression (P<0.001, all). The mRNA expression of smooth muscle (SM) α-actin was significantly increased in all TPNS groups (P<0.005, for all doses) and the protein expression was significantly increased in the medium (P=0.006) and high dose TPNS (P=0.002) groups compared to the injury group. All the TPNS doses significantly decreased the mRNA expression of c-fos (P<0.001). The medium and high dose TPNS groups significantly suppressed the upregulation of pERK1/2 protein in the NIA (P<0.025) and MA (P<0.004). TPNS dose-dependently inhibited balloon injury-induced activation of pERK/p38MAPK signaling in the carotid artery. TPNS could be a promising agent in inhibiting cell proliferation following vascular injuries.